NMR and fluorescence spectroscopy approaches to secondary and primary active multidrug efflux pumps. (1st August 2005) - Lorch, M.; Lehner, I.; Siarheyeva, A.; Basting, D.; Pfleger, N.; Manolikas, T.; Glaubitz, C.
Abstract : Multidrug efflux pumps are found in all major transporter families. Along with a lack of three-dimensional structure information, the mechanism of drug recognition, energy coupling with drug translocation and the catalytic cycle are so far not understood. In the present study, we present first data of a fluorescence-based assay to study the pH-gradient-mediated activity of the multidrug antiporter EmrE, by co-reconstitution with the light-driven proton pump bacteriorhodopsin. In addition to biochemical approaches, the emerging technique, solid-state NMR, can be used for the investigation of these transporters. A number of experiments based on MAS (magic angle sample spinning) NMR are available to provide data on protein structure and dynamics, drug binding and protein–lipid interactions. However, these experiments dictate a number of constraints with respect to sample preparation that will be discussed for proteins from the SMR (small multidrug resistance transporter) family. In addition, 2 H-NMR is used to probe protein mobility of Lactococcus lactis ABC transporter, LmrA.